(untitled) (Medical Forum Monthly, 2021)
Objective: To estimate the frequency of raised ALT in T2DM patients of Quetta and evaluate the risk factors. Study Design: A cross-sectional, prospective study Place and Duration of Study: This study was conducted at the conducted in the department of Internal Medicine, Sandeman Provincial Hospital Quetta for a period of six months from Jan to June 2015. Materials and Methods: The study was approved from institutional review board. Patients of both genders diagnosed type 2 diabetes mellitus were included after attaining informed consent. Serum ALT levels were done for all patients in the hospital laboratory. Demographic and clinical characteristics were recorded. Data was entered and analyzed using SPSS v. 18.0. Results: There were 144 patients in the study –37 (25.7%) women and 107 (74.3%) men. Their mean age was 43.8 ± 7.2 years. Elevated ALT levels were seen in 30 (20.8%) patients of T2DM. Patient gender, body mass index, and duration of diabetes were not statistically related to elevated ALT levels in patients of T2DM (p>0.05). Conclusion: Serum alanine aminotransferase was frequently high in patients of type 2 diabetes mellitus. It was not associated with gender, body mass index, or duration of diabetes.